2,2′-(Diselane-1,2-diyl)dinicotinamide N,N′-dimethylformamide disolvate - Feng, Aixia (International Union of Crystallography, 2010)
The asymmetric unit of the title compound, C(12)H(10)N(4)O(2)Se(2)·2C(3)H(7)NO, contains two solvent molecules and two half molecules of the dinicotinamide, each of which sits on a center of symmetry passing through the middle of the Se—Se bond. In each molecule, the two pyridyl groups and diseleno group are approximately coplanar (r.m.s. deviations from planarity for all non-H atoms = 0.011 and 0.008 Å in the two molecules). Intermolecular N—H⋯O hydrogen bonds stablilize the crystal packing.